High spatiotemporal variability of bacterial diversity over short time scales with unique hydrochemical associations within a shallow aquifer. (1st November 2019) - Zelaya, Anna J.; Parker, Albert E.; Bailey, Kathryn L.; Zhang, Ping; Van Nostrand, Joy; Ning, Daliang; Elias, Dwayne A.; Zhou, Jizhong; Hazen, Terry C.; Arkin, Adam P.; Fields, Matthew W.
Abstract: Understanding microbial community structure and function within the subsurface is critical to assessing overall quality and maintenance of groundwater; however, the factors that determine microbial community assembly, structure, and function in groundwater systems and their impact on water quality remains poorly understood. In this study, three shallow wells (FW301, FW303, FW305) in a non-contaminated shallow aquifer in the ENIGMA-Oak Ridge Field Research Center (Oak Ridge, TN) were sampled approximately 3 times a week over a period of three months to measure changes in groundwater geochemistry and microbial diversity. It was expected that the sampled microbial diversity from two historic field wells (FW301, FW303) would be relatively stable, while diversity from a newer well (FW305) would be less stable over time. The wells displayed some degree of hydrochemical variability over time unique to each well, with FW303 being overall the most stable well and FW301 being the most dynamic based upon dissolved oxygen, conductivity, and nitrate. Community analysis via ss-rRNA paired-end sequencing and distribution-based clustering revealed higher OTU richness, diversity, and variability in groundwater communities of FW301 than the other two wells for diversity binned over all time points. Microbial community composition of a given well was on average > 50% dissimilar to any other well at a given time (days), yet, functional gene diversity as measured with GeoChip remained relatively constant. Similarities in community structure across wells were observed with respect to the presence of 20 shared bacterial groups in all samples in all wells, although at varying levels over the tested time period. Similarity percentage (SIMPER) analysis revealed that variability in FW301 was largely attributed to low abundance, highly-transient populations, while variability in the most hydrochemically stable well (FW303) was due to fluctuations in more highly abundant and frequently present taxa. Additionally, the youngest well FW305 showed a dramatic shift in community composition towards the end of the sampling period that was not observed in the other wells, suggesting possible succession events over time. Time-series analysis using vector auto-regressive models and Granger causality showed unique relationships between richness and geochemistry over time in each well. These results indicate temporally dynamic microbial communities over short time scales, with day-to-day population shifts in local community structure influenced by available source community diversity and local groundwater hydrochemistry. Graphical abstract: Image 1 Highlights: Bacterial community of a given well was >50% dissimilar to any other tested well and time point. Functional gene diversity as measured with GeoChip remained relatively constant. Granger-causality analysis showed relationships between species richness and hydrochemistry.